Improving Human Resources and Supporting Local SMEs through the Digitalization of the Keranggan Ecotourism Village Business in South Tangerang - Abdul Haris Muchtar; Zulfikar Said Agil Sidiki; Arsa Samrotul Fuadah; Aulia Islami Ansar; Eldrian Addin Naufal; Hana Hanifah; Khayla Qalisya; Sayyidah Aisyah Al-Humairah Ahmad (SocietalServe: Journal of Community Engagement and Services, 2024)
The community empowerment program at Keranggan Ecotourism Village identified several challenges, including low productivity, limited information access, and insufficient promotional facilities, resulting in a lack of awareness about the village's offerings. In response, a team comprising faculty and students from ESQ Business School conducted a tridharma activity focused on digital marketing, particularly for Keranggan Snack, a local home industry product aiming for expanded sales. This initiative aimed to leverage social media platforms to enhance product outreach and facilitate the promotion of Keranggan Ecotourism products to local SMEs, optimizing social media for broader audience reach. Additionally, the team facilitated the promotion of Keranggan Ecotourism products at various external events, aligning with Indonesia Emas 2045's vision. The primary objectives were to increase awareness and branding, assist local SMEs in boosting sales, and provide promotional platforms for Keranggan Ecotourism. This multifaceted approach aimed to address fundamental issues and propel Keranggan Ecotourism towards sustainable growth. Through education on digital marketing and active promotion, the program sought to overcome obstacles and elevate the visibility and economic viability of Keranggan Ecotourism Village beyond its immediate surroundings. By providing a platform for wider recognition and engagement, the initiative aimed to contribute to the village's economic development and environmental conservation efforts.